2003
DOI: 10.1016/s0735-1097(02)02953-4
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and other inflammatory risk markers in acute coronary syndromes

Abstract: Markers of myocyte necrosis such as cardiac troponin or creatine kinase-myocardial band are invaluable tools for risk stratification among patients presenting with acute coronary syndromes (ACS). Nonetheless, many patients without any evidence of myocyte necrosis may be at high risk for recurrent ischemic events. In consideration of the important role that inflammatory processes play in determining plaque stability, recent work has focused on whether plasma markers of inflammation may help improve risk stratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
203
2
12

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(225 citation statements)
references
References 50 publications
8
203
2
12
Order By: Relevance
“…We examined biomarkers that represent distinct phases of the ACS spectrum, such as inflammation, endothelial and myocardial dysfunction. Inflammation is thought to play an important role in the events preceding plaque rupture, with many publications documenting the role of CRP in ACS [26]. However, earlier mediators of inflammation, for example IL-6, not only result in CRP production by the liver [26] but IL-6 concentrations have also been reported to be derived from cardiac sources in ACS patients [6,27].…”
Section: Discussionmentioning
confidence: 99%
“…We examined biomarkers that represent distinct phases of the ACS spectrum, such as inflammation, endothelial and myocardial dysfunction. Inflammation is thought to play an important role in the events preceding plaque rupture, with many publications documenting the role of CRP in ACS [26]. However, earlier mediators of inflammation, for example IL-6, not only result in CRP production by the liver [26] but IL-6 concentrations have also been reported to be derived from cardiac sources in ACS patients [6,27].…”
Section: Discussionmentioning
confidence: 99%
“…HS-CRP and IL-6 are markers of systemic inflammation and independent predictors of cardiovascular disease in healthy women. Recent data suggest that HS-CRP plays an active role in atherogenesis [24]. A study by Burns et al [25] has reported non-significant effect of omega-3 fatty acids on HS-CRP levels.…”
Section: Discussionmentioning
confidence: 99%
“…13,18 Several variables seem to interfere with the results provided from commercially available kits, such as temperature, coating antibody affinity, type of material analyzed, among others. 19 In addition, there are no definitive data establishing the cut point value of MPO from which it is a predictor of cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…CRP was a mortality predictor however, not capable of early identification of a high risk subgroup independently of troponin, as suggested in previous studies. 6,11,19 It seems that markers of necrosis are more related to the extension of myocardial damage and early risk, and inflammatory markers probably identify a profile at higher risk of plaque vulnerability and late events.…”
Section: Discussionmentioning
confidence: 99%